2021
DOI: 10.1186/s40560-021-00538-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of failure with high-flow nasal oxygen therapy in COVID-19 patients with acute respiratory failure: a multicenter observational study

Abstract: Purpose We aimed to describe the use of high-flow nasal oxygen (HFNO) in patients with COVID-19 acute respiratory failure and factors associated with a shift to invasive mechanical ventilation. Methods This is a multicenter, observational study from a prospectively collected database of consecutive COVID-19 patients admitted to 36 Spanish and Andorran intensive care units (ICUs) who received HFNO on ICU admission during a 22-week period (March 12-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 29 publications
8
40
0
1
Order By: Relevance
“…Regarding ROX index cut-off points to predict success of HFNC therapy in COVID-19, different studies reported similar points to those proposed by Roca et al 27 and Hu et al11, with a population similar to ours in terms of demographics and comorbidities, concluded that 6 hours after HFNC onset with a cut-off point at 5.55 was the most suitable predictor of HFNC success, albeit with a relatively low sensitivity (61.1%) and relatively high specificity (84.6%); in contrast, in the present study the best predictor of HFNC success is the ROX index 24h after therapy onset, with a cut-off point of 5.35, which yielded better results in sensitivity, specificity, PPV, NPV and AUC than those proposed by other studies.10, 11, 13, 28 Recently have been published prospective studies evaluating utility of ROX index in COVID. 29 , 30 , 31 Mellado-Artigas et al, 29 in a multicenter prospective study that included 259 patients with severe pneumonia due to SARS-CoV-2 who reveived HFNC at ICU admission, found that baseline non-respiratory Sequential Organ Failure Assessment (SOFA) score and ROX index were associated with endotracheal intubation and mechanical ventilation. Suliman et al, 30 in a prospective study that included 69 patients with moderate and severe COVID found that ROX index measured on the first day of admission was independent predictor factor of intubation with a cut-off point <25.26; a very high cut-off point is striking in this study, 30 fact for which it was not included in a recent meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ROX index cut-off points to predict success of HFNC therapy in COVID-19, different studies reported similar points to those proposed by Roca et al 27 and Hu et al11, with a population similar to ours in terms of demographics and comorbidities, concluded that 6 hours after HFNC onset with a cut-off point at 5.55 was the most suitable predictor of HFNC success, albeit with a relatively low sensitivity (61.1%) and relatively high specificity (84.6%); in contrast, in the present study the best predictor of HFNC success is the ROX index 24h after therapy onset, with a cut-off point of 5.35, which yielded better results in sensitivity, specificity, PPV, NPV and AUC than those proposed by other studies.10, 11, 13, 28 Recently have been published prospective studies evaluating utility of ROX index in COVID. 29 , 30 , 31 Mellado-Artigas et al, 29 in a multicenter prospective study that included 259 patients with severe pneumonia due to SARS-CoV-2 who reveived HFNC at ICU admission, found that baseline non-respiratory Sequential Organ Failure Assessment (SOFA) score and ROX index were associated with endotracheal intubation and mechanical ventilation. Suliman et al, 30 in a prospective study that included 69 patients with moderate and severe COVID found that ROX index measured on the first day of admission was independent predictor factor of intubation with a cut-off point <25.26; a very high cut-off point is striking in this study, 30 fact for which it was not included in a recent meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 121 A single multicentre observational study identified the SOFA score and the ROX index as predictive tools for respiratory failure and endotracheal intubation during HFNOT in COVID-19. 122 Moreover, in the early stage, when elastance is relatively preserved, respiratory rate is not particularly high, but tidal volumes could be. 123 Consequently, transpulmonary pressure and changes in pleural pressure are preponderant, with possible haemodynamic consequences.…”
Section: How Can P-sili Be Prevented?mentioning
confidence: 99%
“…Several other tools have been used to predict failure of HFNC particularly the ROX index which has shown promise as its role has been replicated in several studies in diverse settings. [21] However the most appropriate cut-off value for ROX to optimally predict HFNC failure varies widely in in ward (ROX cut-off of 2.2[9], 5.5 [22]and 5.9 [23]) as well as ICU settings (4.8 [24] and 5.37 [25]). Unfortunately, the retrospective nature of the present study did not allow us to track the ROX consistently in all our patients .…”
Section: Discussionmentioning
confidence: 99%